Pediatric Ventilator-Associated Events: Analysis of the Pediatric Ventilator-Associated Infection Data. Issue 12 (December 2018) - Willson, Douglas F.; Hall, Mark; Beardsley, Andrew; Hoot, Michelle; Kirby, Aileen; Hays, Spencer; Erickson, Simon; Truemper, Edward; Khemani, Robinder
Abstract : Objectives: To compare the prevalence of infection applying the proposed pediatric ventilator-associated events criteria versus clinician-diagnosed ventilator-associated infection to subjects in the pediatric ventilator-associated infection study. Design: Analysis of prospectively collected data from the pediatric ventilator-associated infection study. Setting: PICUs of 47 hospitals in the United States, Canada, and Australia. Patients: Two-hundred twenty-nine children ventilated for greater than 48 hours who had respiratory secretion cultures performed to evaluate for suspected ventilator-associated infection. Interventions: None. Measurements and Main Results: Applying the proposed pediatric ventilator-associated event criteria, 15 of 229 subjects in the ventilator-associated infection study qualified as "ventilator-associated condition" and five of 229 (2%) met criteria for "infection-related ventilator-associated complication." This was compared with 89 of 229 (39%) diagnosed as clinical ventilator-associated infection (Kappa = 0.068). Ten of 15 subjects identified as ventilator-associated condition did not meet criteria for infection-related ventilator-associated complication primarily because they did not receive 4 days of antibiotics. Ventilator-associated condition subjects were similar demographically to nonventilator-associated condition subjects and had similar mortality (13% vs 10%), PICU-free days (6.9 ± 7.7; interquartile range, 0–14 vs 9.8 ± 9.6; interquartile range, 0–19; p = 0.25), but fewer ventilator-free days (6.6 ± 9.3; interquartile range, 1–15 vs 12.4 ± 10.7; interquartile range, 0–22; p = 0.04). The clinical ventilator-associated infection diagnosis in the ventilator-associated infection study was associated with fewer PICU-free days but no difference in mortality or ventilator-free days. Conclusions: The ventilator-associated event criteria appear to be insensitive to the clinical diagnosis of ventilator-associated infection. Differentiation between ventilator-associated condition and infection-related ventilator-associated complication was primarily determined by the clinician decision to treat with antibiotics rather than clinical signs and symptoms. The utility of the proposed pediatric ventilator-associated event criteria as a surrogate for ventilator-associated infection criteria is unclear. Abstract : Supplemental Digital Content is available in the text.